Contribution Of Sustainable Innovation To Supporting Competitiveness Company Case Of "danone" Company - Derar, Lamine; Merimet, Adila (جامعة الوادي - University of Eloued, 2022)
This study aims to show the role of innovation as a basic mechanism in enhancing the sustainability of company, supporting its competitiveness, and building a new business model that depends on sustainability and achieves profitability at the same time. And then to clarify the contribution of sustainable innovation to support competitiveness through a case study of "Danone" company which works in the field of food industry during the period (2009 - 2019). The study concluded that the greater interest in integrating sustainable innovations into the company production or commercial activity, the more positively this will be reflected on its performance and consumer behavior towards its products, thus raising its market share, which reflects an increase in company competitiveness. Jel Classification Codes : O30. Q5 ملخص: تهدف هذه الدراسة إلى تبيان دور الابتكار كآلية أساسية في تعزيز استدامة الشركة ودعم تنافسيتها وبناء نموذج أعمال جديد يعتمد الاستدامة ويحقق الربحية في نفس الوقت، لتناول هذا الموضوع والإجابة على الإشكالية المطروحة تم التطرق إلى نبذة حول أهمية تحول الشركة إلى الاستدامة، الابتكار المستدام وتنافسية المؤسسة، ;ومن ثم توضيح مساهمة الابتكار المستدام في دعم التنافسية من خلال دراسة حالة لشركة "دانون" الناشطة في مجال الصناعات الغذائية خلال الفترة من سنة 2009 إلى 2019 . وقد خلصت الدراسة إلى أنه كلما زاد الاهتمام بإدماج الابتكارات المستدامة في النشاط الإنتاجي أو التجاري في الشركة كلما انعكس ذلك إيجابا على أدائها وعلى سلوك المستهلكين اتجاه منتجاتها وبالتالي رفع حصتها السوقية مما يعبر على زيادة تنافسيتها. تصنيفات JEL: O30. Q5
مقال
Keywords: sustainability ; sustainable innovation ; competitiveness ; business model ; Danone company